Підвищення капіталізації та розвиток промислових підприємств на основі адаптаційного підходу - Солод, М.А. (Стратегія і механізми регулювання промислового розвитку, 2014)
Розглянуто можливості використання адаптаційного підходу до формування на промисловому підприємстві механізму протистояння кризовим явищам з метою підвищення його капіталізації і стійкості функціонування. Показано, що прискорення темпів змін у зовнішньому і внутрішньому середовищі привело до масштабного залучення промислового сектору України у процеси перетворень, які потребують розробки і реалізації нового інструментарію, адекватного глобалізаційній і постіндустріальній парадигмі часу і викликам посткризового періоду. Рассмотрены возможности использования адаптационного подхода к формированию на промышленном предприятии механизма противостояния кризисным явлениям c целью повышения его капитализации и устойчивости функционирования. Показано, что ускорение темпов изменений во внешней и внутренней среде привело к масштабному вовлечению промышленного сектора Украины в процесс преобразований, требующих разработки и реализации нового инструментария, адекватного глобализационной и постиндустриальной парадигме времени и вызовам посткризисного периода. The article is devoted to the analysis of methodological approaches to the evaluation of the industrial enterprises adaptive capacity. The results of industrial sector working in the conditions of necessity of overcoming of consequences of world financial and economic crisis are analyses.Grounded, that changes in the market conditions of Ukrainian industrial complex working brings changes in the environment of transformations which need development and realization of new economic instruments, adequate globalization and postindustrial paradigm of time and calls of postcrisis period. It is well proven as a result of the conducted analysis, that development of modern adaptive mechanisms is an important step on the way of overcoming of consequences of world financial and economic crisis and decision of tasks modernization domestic industrial sector.Based on the investigation and generalization of the contemporary methodological approaches to creation and realization of adaptive strategies and analyses practice of their application, the ways of their industrial enterprises using are determined. Development of the methods of industrial enterprises overcoming from the crisis state with the adaptive approach will give possibility not only to promote efficiency of functioning and capitalization of national industrial sector but also, as a result, will assist more steady development of economy of Ukraine on the whole.